Simulation of 5-bit thermometer-to-binary encoders for two different CMOS technology: article / Mohamad Aizzat Zulkeple - Zulkeple, Mohamad Aizzat (2012)
Digital encoders has become bottleneck for high speed Flash-ADC architectures. This paper studies two different 5-bit thermometer-to-binary encoders that suitable for flash analog-to-digital converter. Types of thermometer-to-binary code (TC-to-BC) encoders being studied are ROM-based encoder and Multiplexer-based encoder. Both encoders are designed based on 0.18µm and 0.6µm CMOS technology each. The comparative study between 0.18µm and 0.6µm CMOS technology of both encoders design were done based on power consumption, delay analysis and layout area to determined suitable implementation for Flash ADCs. Simulation and layout design of both encoders were done on Silvaco EDA tools (Gateway and Expert).